Tourist Infrastructure Provision Versus Successful Destinations Case Tudy Langkawi Island. - Jusoh, Jamil; Mohamed, Badaruddin (2006)
Malaysian government has been spending more than US86 million from its annual budget every year for tourism promotion. Since tourism has been identified as the second most important sector of the economy after manufacturing, nearly 30% of the budget allocation is channeled towards physical development, providing infrastructure and services.